Effect of miR-19b-3p on Th17/Treg immune balance in membranous nephropathy mice by targeting the STAT1 signaling pathway - Song Xiao-wei; Quan Zheng-li; Zang Hua-long; Guo Cheng-kun (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the effect of microRNA-19b-3p （miR-19b-3p） on T helper 17 （Th17）/regulatory T （Treg） immune balance in membranous nephropathy （MN） mice by targeting the regulation of signal transducer and activator of transcription 1 （STAT1） signaling pathway.MethodsThe mice were randomly grouped into the control group， MN group， MN+agonist （agomir）-negative control （NC） group， and MN+miR-19b-3p agomir group according to random number table method， with 10 mice in each group. Cationic bovine serum albumin was used to induce the MN model. The 24 hour urinary total protein （24 hUTP）， serum total protein （TP）， albumin （Alb）， creatinine （Scr）， and blood urea nitrogen （BUN） were measured. Real-time fluorescence quantitative polymerase chain reaction （RT-qPCR） was applied to detect the mRNA expressions of miR-19b-3p and STAT1 in renal tissue. The hematoxylin and eosin （H&E）， Masson， and periodic acid-Schiff （PAS） staining were used to observe pathological changes in renal tissue. Immunoglobulin G （IgG） deposition was observed by immunofluorescence staining. Enzyme-linked immunosorbent assay （ELISA） was applied to detect serum levels of interleukin （IL）-17， IL-22， IL-10， and transforming growth factor-β （TGF-β）. Flow cytometry was applied to detect the proportions of Th17 and Treg cells. Western blot was applied to detect the protein expressions of STAT1， IL-17， and forkhead box transcription factor P3 （Foxp3）. Dual luciferase reporter assay was applied to detect the targeting relationship between miR-19b-3p and STAT1.ResultsCompared with the control group， mice in the MN group and MN+agomir-NC group showed severe glomerular injury， obvious deposition of interstitial collagen fibers， increased basement membrane thickness， granular deposition of IgG in glomerular capillary loops， significantly higher 24 hUTP ［（103.62 ± 12.47）μg、（108.93 ± 14.15）μg vs （11.26 ± 2.14）μg］， Scr ［（68.42 ± 7.01）μmol/L、（69.57 ± 7.13）μmol/L vs （37.82 ± 3.96）μmol/L］， BUN ［（13.59 ± 1.46）mmol/L、（13.83 ± 1.39）mmol/L vs （6.15 ± 0.74）mmol/L］， IL-17［（126.43 ± 13.95）ng/L、（118.57 ± 13.83）ng/L vs （54.72 ± 5.83）ng/L］， IL-22［（288.63 ± 29.71）ng/L、（293.47 ± 30.62）ng/L vs （136.82 ± 15.07）ng/L］， proportion of Th17 cells ［（3.39 ± 0.42）%、（3.41 ± 0.38）% vs （1.02 ± 0.11）%］， Th17/Treg ［（2.46 ± 0.27）、（2.44 ± 0.29） vs （0.24 ± 0.03）］， protein level of IL-17［（0.95 ± 0.10）、（0.97 ± 0.11） vs （0.30 ± 0.04）］， protein level of STAT1 ［（1.28 ± 0.14）、（1.25 ± 0.12） vs （0.41 ± 0.05）］ and mRNA level of STAT1 ［（1.72 ± 0.19）、（1.75 ± 0.18） vs （1.01 ± 0.11）］， but significantly lower TP ［（46.28 ± 4.93）g/L、（45.72 ± 4.76）g/L vs （57.24 ± 5.83）g/L］， Alb ［（28.36 ± 2.91）g/L、（27.55 ± 2.83）g/L vs （35.94 ± 3.85）g/L］， miR-19b-3p ［（0.38 ± 0.06）、（0.35 ± 0.05） vs （1.00 ± 0.10）］， IL-10 ［（71.92 ± 7.36）ng/L、（75.83 ± 7.79）ng/L vs （182.05 ± 19.36）ng/L］， TGF-β［（115.92 ± 13.62）ng/L、（107.84 ± 12.68）ng/L vs （235.17 ± 26.39）ng/L］， proportion of Tregs ［（1.38 ± 0.17）%、（1.40 ± 0.16）% vs （4.21 ± 0.48）%］， and protein level of Foxp3 ［（0.42 ± 0.05）、（0.41 ± 0.06）比（0.86 ± 0.09）］ （P<0.05）. Compared with the MN group and MN+agomir-NC， mice in the MN+miR-19b-3p agomir group had significantly alleviated renal tissue damage， reduced interstitial collagen fiber deposition and basement membrane thickening， decreased IgG deposition， lower 24 hUTP ［（51.64  ± 6.83）μg vs （103.62 ± 12.47）μg、（108.93 ± 14.15）μg］， Scr［（42.04 ± 4.83）μmol/L vs （68.42 ± 7.01）μmol/L、（69.57 ± 7.13）μmol/L］， BUN ［（6.15 ± 0.74）mmol/L vs （13.59 ± 1.46）mmol/L、（13.83 ± 1.39）mmol/L］， IL-17 ［（68.51 ± 7.26）ng/L vs （126.43 ± 13.95）ng/L、（118.57 ± 13.83）ng/L］， IL-22 ［（151.86 ± 17.42）ng/L vs （288.63 ± 29.71）ng/L、（293.47 ± 30.62）ng/L］， proportion of Th17 cells ［（1.81 ± 0.21）% vs （3.39 ± 0.42）%、（3.41 ± 0.38）%］， Th17/Treg ［（0.56 ± 0.07） vs （2.46 ± 0.27）、（2.44 ± 0.29）］， protein level of IL-17［（0.46 ± 0.06） vs （0.95 ± 0.10）、（0.97 ± 0.11）］， protein level of STAT1［（0.57 ± 0.06） vs （1.28 ± 0.14）、（1.25 ± 0.12）］ and mRNA level of STAT1［（1.23 ± 0.14） vs （1.72 ± 0.19）、（1.75 ± 0.18）］， but higher TP［（55.94 ± 5.73）g/L vs （46.28 ± 4.93）g/L、（45.72 ± 4.76）g/L］， Alb ［（34.06 ± 3.72）g/L vs （28.36 ± 2.91）g/L、（27.55 ± 2.83）g/L］， miR-19b-3p ［（0.83 ± 0.09） vs （0.38 ± 0.06）、（0.35 ± 0.05）］， IL-10［（164.82 ± 17.39）ng/L vs （71.92 ± 7.36）ng/L、（75.83 ± 7.79）ng/L］， TGF-β［（213.82 ± 22.71）ng/L vs （115.92 ± 13.62）ng/L、（107.84 ± 12.68）ng/L］， proportion of Tregs ［（3.26 ± 0.37）% vs（1.38 ± 0.17）%、（1.40 ± 0.16）%］， and protein level of Foxp3［（0.71 ± 0.08） vs （0.42 ± 0.05）、（0.41 ± 0.06）］ （P<0.05）.ConclusionMiR-19b-3p may restore Th17/Treg immune balance in MN mice and improve renal injury by targeting the regulation STAT1.